How Tourists’ Perception Affects Travel Intention: Mechanism Pathways and Boundary Conditions - Jiang, Xiufang; Qin, Jianxiong; Gao, Jianguo; Gossage, Mollie G. (Frontiers in Psychology, 2022)
Tourist subjectivities have an important affect on behavioral intentions. Under the background of normalization, tourism decision-making manifests primarily in tourists’ individual preferences, which has led much research to ignore the importance of other subjective factors, as well as objective environmental factors. In the COVID-19 era, tourism behavior’s social attributes have become more prominent; the effect of important others or organizations’ attitudes toward tourism behavior, as well as personal knowledge, ability, and experience in preventing and controlling tourism risks is evident. This study integrates KAB, PRT, SIT, and PBT theories, along with a comprehensive framework method, to construct an integrated model exploring the impact of knowledge, identity, and perceived risk on travel intention, to analyze its pathways and effects, to resolve the issue of mechanism, to analyze the moderating effect of past travel experience, and to answer the problem of boundary conditions. It finds that knowledge, perceived risk, and identity have a significant positive impact on travel intention; travel attitudes, subjective norms, and perceived control mediate the influence of knowledge, perceived risk, and identity on travel intention; these mechanism pathways do not always exist. The positive adjustment of past travel experience shows that repeat visitors have a greater impact than newcomers and potential tourists.